2018
DOI: 10.1139/apnm-2017-0453
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high-intensity interval training and moderate-intensity continuous training on sedentary time in overweight and obese adults

Abstract: High-intensity interval training (HIIT) elicits health benefits but it is unclear how HIIT impacts sedentary behaviour. In this preliminary study, we compared the effects of supervised HIIT or moderate-intensity continuous training (MICT) on sedentary time in overweight/obese adults. In both groups, percentage of time spent in sedentary activities was significantly reduced during the supervised exercise intervention (time main effect, P = 0.03), suggesting that both HIIT and MICT replaced time spent previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
3
6
0
Order By: Relevance
“…In fact, not only the results did not show an increase in sedentary behaviors, as women from the HIIT group significantly reduced their sitting time from baseline to the last month of the intervention. Extending previous observations in this patient group, 15 and similarly to what was found in healthy individuals, 21,31,32 patients with T2D appear not to increase sedentary behavior in response to a longer…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In fact, not only the results did not show an increase in sedentary behaviors, as women from the HIIT group significantly reduced their sitting time from baseline to the last month of the intervention. Extending previous observations in this patient group, 15 and similarly to what was found in healthy individuals, 21,31,32 patients with T2D appear not to increase sedentary behavior in response to a longer…”
Section: Discussionsupporting
confidence: 88%
“…A recent 10‐month randomized clinical trial including aerobic exercise (5 days/wk at either 400 kcal per session or 600 kcal per session) found no compensatory decreases in non‐exercise PA. Similar to our observations, overweight and obese individuals do not became less physically active or spend more time in sedentary pursuits in response to an exercise intervention . Two previous trials that also considered an extended exercise intervention (8‐month) concluded that in middle‐aged overweight or obese adults, PA energy expenditure increased and that there was no compensatory decrease in non‐exercise PA …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations